Brief online surveys to monitor and evaluate facilitated peer support groups for caregivers of children with special needs. (April 2015) - Wynter, Karen; Hammarberg, Karin; Sartore, Gina-Maree; Cann, Warren; Fisher, Jane
Highlights: Facilitated peer support groups exist for caregivers of children with special needs. Caregivers may have positive and/or negative experiences of participating in groups. Caregivers have limited time to provide essential feedback to program planners. Brief, online surveys provide a feasible mechanism for ongoing monitoring and evaluation. Online surveys can provide feedback on caregivers' expectations and experiences. Abstract: Background: There have been few systematic evaluations of experiences of participating in peer support groups for parents and other caregivers of children with special needs. In Australia, facilitated groups are available to caregivers in community settings, through a nationally funded program, MyTime. Mechanisms for ongoing monitoring and evaluation have not yet been instituted. Aim: To establish whether brief, online surveys can be used for monitoring and evaluating peer support groups for caregivers of children with special needs. Methods: Two brief, online surveys, with both fixed-choice and open-ended questions, were developed. All caregivers who attended any MyTime group during a 1-month period were invited to participate. Results: Of 89 caregivers who expressed interest in participating, 54 and 31 respondents completed respectively. Respondents represented a variety of backgrounds and circumstances. Responses revealed both positive and negative aspects of group participation. Linked data on expectations and experiences provided important feedback for the program. Conclusion: Brief, online surveys are a suitable mechanism for ongoing monitoring and evaluation of peer support group programs for caregivers.